A method to evaluate the performance of institutions based on data envelopment analysis method with qualitative data and emphasis on OCB - mohammad javad hossainzadeh saljughi (مدیریت نوآوری و راهبردهای عملیاتی)
Purpose: Organisational Citizenship Behaviour (OCB) is one of the important concepts that has been used as an effective factor in the success of organisations in recent years. Despite the proven effect of OCB on the effectiveness and efficiency of the organisation, the appropriate method to determine the extent of its effect is less known. OCB is a qualitative indicator as an output in performance evaluation. In this article, we measure the effect of the OCB quality index on the efficiency of institutions using the envelopment analysis method of ordinal data without compensatory properties.Methodology: Data coverage analysis is a powerful tool for assessing the performance of decision-making institutions based on a large number of input and output indicators, which can be quantitative or qualitative. Data coverage analysis models have compensatory properties, i.e. the weakness of one index is covered by the strength of another, and efficient institutions do not necessarily have a favourable quality level. This article presents a new method for performance evaluation that includes the quality index of OCB and a modification of the data envelopment analysis model without compensability. Another feature of the proposed model is the ability to separate qualitative and quantitative indicators in the evaluation. In the presented method for ranking institutions, the improvement of quality is considered simultaneously with the reduction of costs without compensability.Findings: In this study, ten public and applied scientific institutions in three cities of the country were evaluated with the proposed model. Four quantitative indicators and one qualitative index of OCB were used in the evaluation.Originality/Value: The OCB index was measured using 1024 questionnaires and the results show the efficiency of 7 institutions. Then, by using the proposed new method, the ranking of institutions with logical results in performance evaluation was achieved. To validate the method, the results of the proposed method were compared with the ranking results of the hierarchical process method.